Walk with a Future Doc program allows Canadian medical students to promote physical activity and health education in local communities - Wilson, Taylor M; Theou, Olga; O’Brien, Myles W (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2024)
Implication StatementMedical student-led walk and talk programs, such as Walk with a Future Doc (WWAFD), provide a means for the medical community and community at-large to interact in a non-clinical setting. This environment can increase attendance accountability, enhance patient-provider relationships, and allow medical professionals to be leading examples of healthy, active living. We demonstrate the positive interest for this program, rationale of participants for joining, and the feasibility of its setup. As one of the only WWAFD programs in Canada, we encourage other medical schools to implement this program to promote continuity of hands-on, community-engaged learning amongst their students.